Future Potential of Exoskeleton in the Malaysian Construction Industry - Fong , Jun Kai; Ahmad Latiffi, Aryani (Research in Management of Technology and Business, 2023)
The construction industry is a physically demanding and labor-intensive industry that requires a lot of manual handling of materials and awkward working postures. The great majority of tasks in construction projects, such as lifting or moving materials, plastering, paving and surfacing, scaffolding, and more, involve a lot of labours. Exoskeleton is a technology that has the potential to decrease the risk of injury of workers in the construction industry. This technology is being implemented widely in developed countries and has the potential to be implemented in developing countries such as Malaysia. Therefore, the objectives of this research are to identify the current level of understanding of the technology, the challenges that exoskeleton will encounter in the Malaysian construction industry and the ways to promote exoskeleton in the industry. This research was carried out through a questionnaire survey. A total of 90 respondents participated in the survey and gave their responses to the questionnaire form. The findings from the survey revealed the future potential of the exoskeleton in the Malaysian construction industry. The level of understanding of exoskeleton in the Malaysian construction industry was at a high level. The main challenge that the exoskeleton will encounter is cost. The cost of this technology involved in acquiring maintaining and updating technology fees. Hence, the respondents agree that the government plays a great role in promoting the use of the exoskeleton in the construction industry. In conclusion, exoskeleton has the potential to contribute to lessening the number of injuries of workers in the construction industry.